Late outcome of Senning and Mustard procedures for correction of transposition of the great arteries. Issue 5 (14th April 2005) - Dos, L; Teruel, L; Ferreira, I J; Rodriguez-Larrea, J; Miro, L; Girona, J; Albert, D C; Gonçalves, A; Murtra, M; Casaldaliga, J
Abstract : Objectives: To evaluate late mortality and morbidity after an atrial switch procedure for correction of transposition of the great arteries (TGA) and to assess predictive factors for adverse outcome. Setting: Tertiary referral centre. Design and patients: Retrospective follow up study of 137 patients surviving hospitalisation for TGA atrial switch procedure (Mustard or Senning) in a single institution and divided into two groups (simple and complex) depending on presurgical anatomy. Several surgical and follow up factors were evaluated during 16.7 (5.6) years' follow up. Results: Late mortality was 5.1% (95% confidence interval 1.37% to 8.84%) with sudden death as the most common cause. No significant difference was found between Mustard and Senning procedures and between the complex and simple groups in terms of mortality. Independent predictive factors for late mortality were a history of supraventricular tachyarrhythmias and advanced New York Heart Association (NYHA) functional class during follow up. A very common finding was development of sinus node dysfunction (47.6%), which had no influence on mortality. There was little need for reintervention (5.1%) and relatively few cases of right ventricular systolic dysfunction (14.6%). During follow up, most patients (96.2%) were in NYHA functional class I–II. Conclusions: Overall long term outcomes of patients with atrial repair of TGA in the present era are encouraging in terms of late mortality and quality of life. Nevertheless, better outcomes may be offered through improved diagnostic methods for right ventricular function and better management of supraventricular tachyarrhythmias.